Using Translation as an Activity in Content-Based Instruction - Melinda Roza (International Conference on Education and Language (ICEL), 2014)
As one of the techniques in foreign language teaching, translation is almost forgotten since this technique cannot be able to make the learner use language actively in terms of speaking and listening. Actually, if translation is used properly, it can be applied in teaching foreign language in the classroom. This study is aimed at giving an idea of using translation as the technique through content-based instruction in university or college. Content-based instruction is the teaching which combines the teaching of foreign language skills and teaching a specific content in the specific field. In this study, the use of translation technique is as one of the activities through content-based instruction. It is assumed that learning a foreign language while studying a specific content related to the learner’s field of study will be more useful and interesting. There are two techniques suggested in this paper: translation activities during the teaching learning process in the classroom and translation activities after the classroom teaching. Then, the specific language skills will be the target in this kind of teaching such as: skimming and scanning, reviewing materials being taught, making question as well as answering, summarizing, presenting, and some other skills related to skills needed while studying. It is hoped that students at university level will be more interesting and creative since the teaching of foreign language is related to their field.